The Intersections of Conspiracy Theories and Postmodern Thought in the Long 1960s - Florian Andrei VLAD (ACROSS)
This article examines the intersections of postmodern thought and conspiracy theories within the context of the "long 1960s" (roughly 1958-1974). I argue that the period’s pervasive skepticism toward grand narratives and authority, fueled by intellectual trends of the era, as well as by countercultural movements and by events such as the Vietnam War and the Kennedy assassination, created a fertile ground for the proliferation of conspiracy theories. The analysis also explores how this cultural shift was reflected in literature, including novels by Joseph Heller, Kurt Vonnegut, and Thomas Pynchon, and how this phenomenon remains relevant in the present day, in the context of persisting widespread acceptance of conspiracy theories and distrust of authority.